1997
DOI: 10.1364/ol.22.000178
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching of thulium-doped ZBLAN fibers with visible light

Abstract: Photobleaching of darkened thulium-doped ZBLAN fibers is observed after short exposure to visible light. The bleaching process is characterized by a stretched-exponential function of time with an exponent beta independent of both the bleaching intensity and the thulium concentration. The bleaching rate 1/ is also shown to scale linearly with the bleaching intensity and to have a 1/3 -power dependence on the thulium concentration. Incomplete and slow recovery of the color centers is observed in previously bleac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…6 for the stretched exponential fits are consistent with observations by several groups who have studied photobleaching and thermal annealing of color center defects in glasses. Laperle et al 21 observed that an absorption change in a thulium-doped ZBLAN glass fiber induced by infrared laser light was associated with color center formation. Prolonged exposure of the fiber to a visible laser light source resulted in photobleaching of the color centers and an associated decay in the absorption increase.…”
Section: Resultsmentioning
confidence: 99%
“…6 for the stretched exponential fits are consistent with observations by several groups who have studied photobleaching and thermal annealing of color center defects in glasses. Laperle et al 21 observed that an absorption change in a thulium-doped ZBLAN glass fiber induced by infrared laser light was associated with color center formation. Prolonged exposure of the fiber to a visible laser light source resulted in photobleaching of the color centers and an associated decay in the absorption increase.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the excitation of higher levels of Tm 3+ ions via energy transfer processes leads to the creation of color centers that significantly increase the absorption in visible band. Although a few investigations of photodegradation and photobleaching have been conducted [149][150][151][152], so far there still has no effective method to prevent photodegradation occurring in high-power operation of Tm 3+ -doped ZBLAN fiber lasers. Nevertheless, using new pumping schemes [153][154][155][156] can improve the CW performance of Tm 3+ -doped ZBLAN fiber lasers by reducing the pump threshold and increasing the conversion efficiency.…”
Section: Upconversion Er 3+ -Doped Zblan Fiber Lasers the Partial Enmentioning
confidence: 99%
“…However, the rehabilitating rate is limited; what's more, the process usually takes very long time. In order to improve optical transparency and reduce radiation-induced loss in irradiated fiber more efficiently, Thermal-Bleaching method [9][10] and photo-bleaching method [11][12][13][14] are both introduced. Although the thermal-bleaching technique is widely used in glass and photo-bleaching technique is reported in many papers, photo-bleaching technique applied in SMF has not been lucubrated.…”
Section: Introductionmentioning
confidence: 99%